An alternative method for estimating Vs(30) from a shallow shear-wave velocity profile (depth <30 m). Issue 99 (August 2017) - Wang, Su-Yang; Wang, Hai-Yun; Li, Qiang
Abstract: The near-surface travel-time averaged shear-wave velocity to 30 m ( Vs (30)) is a key parameter for ground-motion prediction equations and building codes. In many cases, however, shear-wave velocity profiles do not extend to 30 m. In this article, we propose an alternative method for estimating Vs (30) from a shallow shear-wave velocity profile, using the travel-time averaged shear-wave velocities at two different depths ( Vs ( z 1 ) and Vs ( z 2 ), and z 1 < z 2 <30 m). Using the data from 643 boreholes from the KiK-net in Japan and 135 boreholes from California where the shear-wave velocity profile reaches at least 30 m, the reliability of the proposed method is validated by the correlations between the measured and the estimated Vs (30) and the accuracy of site classification using the estimated Vs (30). The results show that the proposed method can estimate Vs (30) with high accuracy, as the Pearson correlation coefficients between the measured and the estimated V s(30) are greater than 0.99, and the site classification successful rates using the estimated Vs (30) are greater than 94%, whereas z 1 ≥10 m and z 2 ≥20 m. Compared with the method of Wang and Wang (2015), the proposed method has a certain improvement in the accuracy, with higher correlations and accuracy of site classification. Highlights: We propose an alternative method for estimating V s(30) with high accuracy. The proposed method works better than existing methods. The proposed method works well for target depth exceeding 30 m.